Biology of microorganisms on grapes, in must and in wine - König, Helmut, 1950 May 3-; Unden, Gottfried; Fröhlich, Jürgen, Dr (Springer, 2017)
In contrast to previous publications, this book consistently focuses on the biology of wine-associated microbes. An international board of expert wine researchers describes the relevant ecological, physiological and genetic aspects of wine microbiology.
Keywords: Wine and wine making -- Microbiology.; elektronické knihy; electronic books